PREOPERATIVE DENOSUMAB AND FEASIBILITY OF LESS MORBID SURGERY IN CAMPANACCI STAGE 3 GIANT CELL TUMOUR OF BONE - Rasheed, Muhammad Asif; Amin, Muhammad Suhail; Muhammad Sohaib Nadeem,; Chaudhry, Muhammad Nadeem; Areej Fatima, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Giant cell tumour of bone (GCTB) is a rare, locally aggressive benign bone tumour with slight female sex predilection and affecting young adults 20-40 years of age. World health organization (WHO) has recently categorized GCTB as an intermediate malignant tumour. GCTB is known to be driven pathologically via expression of pro-osteoclastic signals by stromal cells. This is mediated precisely via the expression of RANKL by stromal cells acting in an autocrine fashion on RANK receptor-positive osteoclast-like giant cells and their precursors. While the treatment is primarily surgical, we hypothesized that preoperative denosumab therapy facilitates conversion to a less morbid procedure in an aggressive campanacci grade 3 GCTB, otherwise amenable to joint resection and reconstruction/arthrodesis. Methods: A prospective, single arm, interventional study was conducted in Orthopaedics and radiation oncology department of combined military hospital (CMH) Rawalpindi. The duration of study was 36 months. Patients were recruited by purposive sampling technique as per inclusion/exclusion criteria. Denosumab was administered as preoperative adjuvant therapy for 3 months. Pain was assessed utilizing Brief Pain Inventory -Short Form (BPI-SF) and functional status was assessed as per Musculoskeletal tumour society score at baseline and 12 weeks after commencement of denosumab therapy. The intent of surgery pre and post denosumab therapy was ascertained. Results: Total of 23 patients were a part of this study. Mean pain scores and MSTS scores prior to and after denosumab were statistically significant with p-value <0.01. Pre-denusomab, there was inclination towards resection arthroplasty as the treatment procedure (56.5%). After denusomab therapy, intralesional curettage was choice of procedure with intent executed for 78.3% of cases. Conclusion: Denosumab has potential role for giant cell tumour of bone, it makes a less morbid surgery technically feasible. However, recurrence needs to be probed in long term follow up studies.